Progesterone Receptor Expression in Meningiomas: Pathological and Prognostic Implications - Maiuri, Francesco; Mariniello, Giuseppe; de Divitiis, Oreste; Esposito, Felice; Guadagno, Elia; Teodonno, Giuseppe; Barbato, Marcello; Del Basso De Caro, Marialaura (Frontiers in Oncology, 2021)
Abstract Background: The progesterone receptor (PR) is variably expressed in most meningiomas and was found to have prognostic significance. However, the correlation with patient age, tumor location, time to recurrence and pattern of regrowth has scarcely been discussed. Methods: A surgical series of 300 patients with meningiomas is reviewed. The PR expression was classified as: 0. absent; 1. low (<15%); 2. moderately low (16-50%); 3. moderately high (51-79%); 4. high (≥80%). The PR values were correlated with the patient age and sex, meningioma location, WHO grade, Ki-67 MIB1, recurrence rate, pattern of recurrence (local-peripheral versus multicentric diffuse), time to recurrence. Results: The PR expression has shown lower rate of high expression in the elderly group (p=0.032) and no sex difference (including premenopausal versus postmenopausal women), higher expression in medial skull base and spinal versus other locations (p=0.0036), inverse correlation with WHO grade and Ki67-MIB1 (p0.0001). Meningiomas which recurred showed at initial surgery higher rates of low or moderately low PR expression than the not recurrent ones (p=0.0004), whereas the pattern of regrowth was not significant. Higher rates of PR values ≥80% were found in cases with time to recurrence > 5 years (p=0.036). Conclusion: The higher PR expression in medial skull base meningiomas, the significant correlation with the time to recurrence, the lack of difference of PR expression between premenopausal and postmenopausal women and between local-peripheral versus multicentric-diffuse recurrences are the most relevant unreported findings of this study. The rate of PR expression must be included in the routine pathological diagnosis of meningiomas because of its prognostic significance.